Исследование MOSFET-транзисторов в различных герметичных корпусах для поверхностного монтажа - Rubtsevitch, I. I.; Anufriev, L. P.; Kerentsev, A. F. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The assembly processes of MOSFET transistors in the SMD-1 metal-ceramic package were investigated in comparison with the SMD-220 metal-plastic package. Results regarding electrical and thermal parameters are presented. It is shown that the “p-n junction–package” thermal resistance is higher for SMD-1; however, the thermal conductivity consistency of the SMD-1 package components allows for the manufacture of devices with minimal internal stresses and ensures their high hermeticity and reliability under conditions of temperature fluctuations exceeding 300°C.